Reliability of Duo Chrome Test in Different Age Groups Considering Patient Satisfaction as Gold Standard: Doi: 10.36351/pjo.v37i4.1118 - Mazhar, Zehwa; Manzoor, Rabia; Kanwal, Shazia; Iqbal, Ghazala (Pakistan Journal of Ophthalmology, 2021)
Purpose: To check the reliability of the duo-chrome test in different age groups after best correction. Study Design: Descriptive, Cross Sectional Study. Place and Duration of Study: College of Ophthalmology and Allied Vision Sciences. King Edward Medical University, Lahore from September 2019 – December 2019. Methods: Forty two cooperative patients of both genders more than 15 years of age were included but patients with poor fixation, any opacity or any other ocular pathology were excluded. Equipment used was Trial box Trial frame Auto-refractor and Snellen Chart. Group 1 composed of 17 patients (15 – 35 years of age). Group 2 (36 – 60 years) had 15 patients and group 3 (age 61-80 years) comprised of 10 patients. Data was collected on self-designed Performa. Duo Chrome was dependent variable and gender was independent variable. Data was analyzed by using statistical package for social science (SPSS22.00) and chi square test was applied. Results: Out 42, 21 patients reported red, 12 reported green and 9 patients reported equally clear in the right eye. P value=0.156 showed that duo chrome test was equally reliable in every age group in the right eye. Similar results with p = 0.755 showed that duo chrome test was equally reliable in every age group in the left eye. Test when performed bilaterally, showed similar results. Out of 42 patients, 32 were satisfied and 10 were not satisfied with the test. Conclusion: Red Green duo-chrome test is equally reliable in all age groups to confirm refraction. Key Words: Duo chrome test, Refraction, Myopia, Hypermetropia.